Late lunch with llamas - Osborne, Mary Pope; Ford, AG (New York Random House Childrens Books, 2007)
"The magic tree house whisks Jack and Annie away to South America, where they must climb Machu Picchu to save a baby llama"--
b
108262
Keywords: Annie -- (Fictitious character from Osborne); Jack -- (Fictitious character from Osborne); Brothers and sisters; Time travel -- .; Space and time; Voyages and travels; Incas; Llamas; Animals -- Infancy; Magic; Tree houses; Machu Picchu Site (Peru); Peru -- History -- To 1548; Historical fiction; Time-travel fiction; Fantasy fiction